2017
DOI: 10.1007/s10729-017-9407-5
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing patient length of stay via new flexible exam room allocation policies in ambulatory care clinics

Abstract: To address prolonged lengths of stay (LOS) in ambulatory care clinics, we analyze the impact of implementing flexible and dynamic policies for assigning exam rooms to providers. In contrast to the traditional approaches of assigning specific rooms to each provider or pooling rooms among all practitioners, we characterize the impact of alternate compromise policies that have not been explored in previous studies. Since ambulatory care patients may encounter multiple different providers in a single visit, room a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…CINAHIL, PUBMED, GOOGLE SCHOLAR, 10 abstract only 5 have the recommendation to reduce LOS in an emergency, most of the studies were recommended the same thing mentioned above. One of the studies strongly recommended developing a protocol or Algorithm for emergency LOS and teaching staff according to Algorithm [11].…”
Section: Discussionmentioning
confidence: 99%
“…CINAHIL, PUBMED, GOOGLE SCHOLAR, 10 abstract only 5 have the recommendation to reduce LOS in an emergency, most of the studies were recommended the same thing mentioned above. One of the studies strongly recommended developing a protocol or Algorithm for emergency LOS and teaching staff according to Algorithm [11].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, previous researchers (Famiglietti et al, 2017;Mustafee et al, 2010) used DES in an outpatient clinic to evaluate and analyze the factors that impact the clinic performance in terms of patient waiting and resource utilization, while another study (Berg et al, 2013) used DES to estimate the effects of noshows on an outpatient clinic in terms of cost. In contrast, implementing DES improvement strategies within outpatient settings is often challenging because of the tremendous amount of data extracted under the conflict of interest between the stakeholders (Eldabi et al, 2007;Matta and Patterson, 2007;Robinson et al, 2012); as a result, improvements with DES tend to be focused on testing suggested new changes by the management in terms of layout, patient flow and resource flow (Demir et al, 2018;Deo et al, 2012;Harper and Gamlin, 2003;Kopach et al, 2007;Vahdat et al, 2018) or it could be focused on performing sensitivity analysis to test the impact of one or a small number of factors on the clinic performance such Lean techniques as the arrival rate, the number of resources hired and sequencing policies (Day et al, 2014;LaGanga and Lawrence, 2007;Lenin et al, 2015;Pan et al, 2015;Rau et al, 2013). In addition, some researchers applied DES to improve the clinical performance based on the effects of appointment scheduling rules and sequencing rules or other soft systems methodology on the clinical performance in terms of patient waiting and resource waiting times (Cayirli et al, 2019(Cayirli et al, , 2006Cayirli and Gunes, 2014;Yang and Cayirli, 2020).…”
Section: Simulation In Health Carementioning
confidence: 99%
“…In other words, constraint set (3) make certain that a provider's clinic schedule will not be segmented during a given day. Constraint set (4) calculates the average number of providers in clinic across the scheduling time frame and constraint set (5) require that the decision variables defined only take on binary values.…”
Section: Constraintsmentioning
confidence: 99%
“…The result is that the traditional approach of assigning clinic resources (e.g., exam rooms) to providers happens less often and provider staffing levels need to be balanced with availability of these shared resources. 5 Finally, as care becomes more interdisciplinary and the use of team-based care models grows, coordination of provider and ancillary staff schedules is an additional necessary consideration in operational planning. Collectively, these characteristics form the challenges in designing modern outpatient care delivery systems and represent the need for decision support approaches that balance these competing operational goals and requirements.…”
mentioning
confidence: 99%